Study of Residual Stresses in I Sectioned bars of Non-Linear WorkHardening Materials under Torsion - Dwivedi, Sandeep; Lal, Radha Krishna; Choubey, V. K.; and et al (Elsevier Ltd, 2015)
This paper deals with the springback problems of I section bars of non-linear work-hardening materials under the torsional loading. Using the deformation theory of plasticity, a numerical scheme based on the finite difference approximation has been proposed. The growth of the elastic-plastic boundary and the resulting stresses while loading, and the springback and the residual stresses after unloading are calculated.
Keywords: Elastic-plastic boundary; Residual stresses; Springback; Torsional loading